Necropsy findings on child abuse in Bogotá, Colombia, between 2000-2005 and 2011-2013 (2015)
Introduction: The purpose of this article is to present the results of research conducted in medicolegal necropsies of children who died of child abuse in Bogotá, Colombia, during two periods between 2000-2005 and 2011-2013. Methodology: Determining causes of death and the pattern of more frequent traumatic injuries, and comparing them with those described in the medical literature. The Bogotá Regional Office of the National Institute of Legal Medicine and Forensic Sciences annually receives about 4,700 bodies, out of which between 8 and 10% are cases of minors. Results: 110 cases of death from childmaltreatment by acts of commission. Ages ranged from 7 days old to 15 years old. Boys accounted for 55% and girls for 45%. The causes of death in these children were head trauma (66.36%), abdominal trauma (29.09%), and asphyxiation (2.73%). Dermal injury traumas were the most frequent injury accompanying the causes of death. Conclusions: 2.67% of deaths of children living in Bogota are caused by child abuse. The causes of death weremainly head trauma, followed by abdominal trauma. The most frequent mechanism of head trauma was acceleration-deceleration. 11.1 % had sexual crime associated. The attackers identified were mostly parents.